VLT observations of the magnetar CXO J164710.2−455216 and the detection of a candidate infrared counterpart. Issue 3 (3rd October 2017) - Testa, V.; Mignani, R. P.; Hummel, W.; Rea, N.; Israel, G. L.
Abstract: We present deep observations of the field of the magnetar CXO J164710.2−455216 in the star cluster Westerlund 1, obtained in the near-infrared with the adaptive optics camera NACO@VLT. We detected a possible candidate counterpart at the Chandra position of the magnetar, of magnitudes J  = 23.5 ± 0.2, H  = 21.0 ± 0.1 and K S  = 20.4 ± 0.1. The K S -band measurements available for two epochs (2006 and 2013) do not show significant signs of variability but only a marginal indication that the flux varied (at the 2σ level), consistent with the fact that the observations were taken when CXO J164710.2−455216 was in quiescence. At the same time, we also present colour–magnitude and colour–colour diagrams in the J, H and K S bands from the 2006 epoch only, the only one with observations in all three bands, showing that the candidate counterpart lies in the main bulk of objects describing a relatively well-defined sequence. Therefore, based on its colours and lack of variability, we cannot yet associate the candidate counterpart to CXO J164710.2−455216. Future near-infrared observations of the field, following up a source outburst, would be crucial to confirm the association with the detection of near-infrared variability and colour evolution.